Modeling studies of corrosion fatigue in a low carbon steel. Issue 1 (1st January 2019) - Kolawole, S. K.; Kolawole, F. O.; Soboyejo, A. B. O.; Soboyejo, W. O.
Abstract: This paper presents the results of the modeling studies of the simultaneous action of applied cyclic stress and the corrosion of low-carbon steel in environments with different pH levels (pH of 3, 5, 8, and 11). The evolution of fatigue cracks from corrosion pits is explored using scanning electron microscopy. The stress concentrations associated with possible cracks emanating from the perimeters of corrosion pits are also studied using finite element analyses. A crack growth model expressed as a function of stress intensity factor range, ΔK and pH of the corrosive media is developed using multivariate statistical modeling. The material removal due to corrosion is also studied. Finally, the results obtained from this work can be used to design against fatigue where machines operate in a corrosive environment.